Pengaruh Kepercayaan Dan Kepuasan Terhadap Tingkat Loyalitas Pelanggan: (Studi Kasus Pada MGS Computer Kota Balikpapan) - Winda Ayuni Rahmawati (Jurnal Publikasi Ilmu Manajemen, 2023)
This study aims to ensure customer trust and satisfaction have an influence on MGS Computer Balikpapan customer loyalty partially or simultaneously (simultaneously). MGS Computer located on Jalan Jalan Letjen S. Parman in Balikpapan Tengah District, Balikpapan City is the location of this research. The source of data used is primary data. The sample in the study amounted to 100 samples. Data collection is carried out by giving questionnaires to MGS Computer customers about customer trust, customer satisfaction and customer loyalty. Data was processed using IBM SPSS (Statistical Package for Social Science) version 26. Hypothesis testing using multiple linear regression analysis techniques. The R2 result showed 0.5880, or 58.8%, which means that 58.8% of the variance in the customer loyalty variable can be explained by the trust and satisfaction variables that have been incorporated into the research model and the remaining 41.2% can be explained by other factors. The findings of the coefficient of determination test show that the variables of customer satisfaction and trust have a positive and significant effect partially or simultaneously on the variable of customer loyalty.